The The Impact of Digitalization on Human Resource Management Practices - Seipalla, Fenska; Liem, Nadia; Siregar, Deorina Roully Gratia; Martdana, Ardhin; Paramarta, Vip (Jurnal Ilmiah Sumber Daya Manusia, 2024)
Human Resource Management (HRM) is a discipline that focuses on managing employees within an organization to achieve the company’s strategic goals. With the advent of the digital era and the Fourth Industrial Revolution, digitalization has become a significant force that has transformed various sectors, including HRM. Understanding the impact of digital transformation on HRM is important for enhancing organizational performance. This article reviews relevant literature related to the main problem addressed. The findings reveal how digital transformation in HRM enhances the efficiency and effectiveness of HR processes by streamlining employee recruitment, selection, orientation, training, and development. Technology also increases employee engagement through self-service portals and communication platforms that facilitate better collaboration and interaction, thereby boosting employee productivity. Digital engagement platforms enhance internal communication, employee satisfaction, and retention by improving interaction and feedback mechanisms. However, digitalization introduces challenges, including concerns over data security and privacy, as well as the need for HR professionals to continually adapt to new technologies. Therefore, companies must understand the potential for both success and failure in digital strategies, especially in Human Resource Management practices. This understanding is crucial for ensuring increased efficiency and competitiveness in the digital era.